Processing of auditory information in forebrain regions after hearing loss in adulthood: Behavioral and electrophysiological studies in a rat model - Johne, Marie; Helgers, Simeon O. A.; Alam, Mesbah; Jelinek, Jonas; Hubka, Peter; Krauss, Joachim K.; Scheper, Verena; Kral, Andrej; Schwabe, Kerstin (Frontiers in Neuroscience, 2022)
Abstract Background: Hearing loss was proposed as a factor affecting development of cognitive impairment in elderly. Deficits cannot be explained primarily by dysfunctional neuronal networks within the central auditory system. We here tested the impact of hearing loss in adult rats on motor, social, and cognitive function. Furthermore, potential changes in the neuronal activity in the medial prefrontal cortex (mPFC) and the inferior colliculus (IC) were evaluated. Methods: In adult male Sprague Dawley rats hearing loss was induced under general anaesthesia with intracochlear injection of neomycin. Sham-operated and naive rats served as controls. Postsurgical acoustically evoked auditory brainstem response (ABR) -measurements verified hearing loss after intracochlear neomycin-injection, respectively intact hearing in sham-operated and naive controls. In intervals of eight weeks and up to nine months after surgery rats were tested for locomotor activity (open field) and coordination (Rotarod), for social interaction and preference, and for learning and memory (4-arms baited 8-arms radial maze test). In a final setting, electrophysiological recordings were performed in the mPFC and the IC. Results: Locomotor activity did not differ between deaf and control rats, whereas motor coordination on the Rotarod was disturbed in deaf rats (P<0.05). Learning the concept of the radial maze test was initially disturbed in deaf rats (P<0.05), whereas retesting every eight weeks did not show long-term memory deficits. Social interaction and preference was also not affected by hearing loss. Final electrophysiological recordings in anaesthetized rats revealed reduced firing rates, enhanced irregular firing, and reduced oscillatory theta band activity (4-8 Hz) in the mPFC of deaf rats as compared to controls (P<0.05). In the IC, reduced oscillatory theta (4-8 Hz) and gamma (30-100 Hz) band activity was found in deaf rats (P<0.05). Conclusions: Minor and transient behavioral deficits do not confirm direct impact of long-term hearing loss on cognitive function in rats. However, the altered neuronal activities in the mPFC and IC after hearing loss indicate effects on neuronal networks in and outside the central auditory system with potential consequences on cognitive function.